EFFECT OF SANKHAPUSHPI (CLITORIA TERNATEA LINN.) CHOORNA IN THE WORKING MEMORY OF CHILDREN (International Journal of Ayurveda and Pharma Research, 2019)
The term “Working memory” refers to the ability of a person to hold information in mind and to manipulate it over short periods of time. Its deficit creates a high risk factor for educational underachievement as it is a better predictor of school performance than IQ. A clinical study was conducted to find out the effect of Sankhapushpi (Clitoria ternatea Linn.) choorna in the working memory of children. The study was conducted as therapeutic, interventional, non randomized, single group assignment, pre and post test and was carried out at the OPD of Dept. of Kaumarabhritya, Government Ayurveda College, Thiruvananthapuram. The study population included children in the age group 7 to 11years of both sexes with working memory deficit for their age when assessed by a clinical psychologist, selected from a population who presented with poor scholastic performance. The tools used were N back tasks for Verbal and Visuospatial Working Memory from NIMHANS Neuropsychological Battery and Visuospatial working memory span task and Working Memory Index tests in Wechsler’s Intelligence Scale. The trial drug, Sankhapushpichoorna was given twice daily in empty stomach in the dose 1-2 gm with plain ghee and honey for 2 months. They were assessed before and after intervention and after 1 month of follow up period and the difference in scores were assessed. Analysis of the data using the most appropriate statistical tests showed significant response (P